ISOLASI DAN UJI TOKSISITAS SENYAWA ALKALOID DARI KULIT BATANG TUMBUHAN Polyalthia rumphii (B) Merr. (ANNONACEAE) - Hakim, Diski Rahman; Teruna, Hilwan Yuda; ', Yuharmen (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
An alkaloid has  been isolated from the stem bark of Polyalthia  rumphii and the toxicity activity was determined using the Brine Shrimp Lethality Test method againts larvae of Artemia salina  Leach. The sample was extracted by maceration method using  n-hexane and methanol  respectively. The dried sample produced  4.19  g  of  n-hexane  extract  and 80.56 g of methanol extract. The methanol extract was  extracted using acid-base method produced  0.04 g  of crude  alkaloids  which  then  was subjected  to  column chromatography  produced  three fractions.  Since the amount of fraction 1 & 3  was insufficient for further purification, only fraction  2 was purified using Sephadex LH-20 to give a  compound  coded as  DK1. The structure of DK1 was determined using 1H-NMR spectroscopy   and indicated that DK1 had aromatic rings and a methoxy group.The toxicity assay showed that  the  extract of methanol and the fraction 2 were toxic with LC50 154.98 and 243.91 ppm, respectively .